The Usage of Information on Costs Classification for Various Purposes of Enterprises’ Activities - Tamulevičienė, Daiva; Mackevičius, Jonas (Information & Media, 2019)
Understanding the essence and significance of costs, as well as the possibilities of how to decrease them, is one of the most important conditions for enterprises to succeed. The article analyzes the nature, importance, and description of costs. The volume, dynamics, and structure of Lithuanian enterprises’ costs for the period of 2013–2017 is provided. Features of costs classification, based on which one can determine on what purposes the information on costs may be used, are systematized. The methodology of the usage of information on costs classification for specific purposes is provided. It is comprised of three stages: 1) the foresight of opportunities for the usage of the information fund of costs classification; 2) the setting of goals for the usage of information on costs classification; 3) the evaluation of the effectiveness of the usage of the information fund of costs classification. The second stage should be considered the most important one in this process, because when the information fund of costs classification is being shaped and used, the set goals determine the need and purpose of such information. Taking this aspect into account, it is suggested to distinguish the three main goals of the information on costs classification: the administration and improvement of the accounting system, the improvement of the enterprise’s management system, as well as the establishment and improvement of the enterprise’s activity results.
Keywords: cost; types of cost; fund of information of cost classification; cost analysis of Lithuanian enterprises